THE ROLE OF WOMEN IN ISLAMIC THOUGHT: GENDER, AGENCY, AND POWER DYNAMICS IN THE QURAN - Achmad Napis; Bilal Aslam; Kiran Iqbal (Yayasan Adra Karima Hubbi, 2026)
The role of women in Islamic thought has been a topic of significant debate, particularly regarding their agency and power dynamics in the Quran. Historically, Islamic interpretations have often placed women in subordinate roles, with their agency constrained within specific boundaries. This research explores how gender roles, power relations, and women’s agency are portrayed in the Quran, analyzing both classical and contemporary feminist interpretations. The study aims to provide a nuanced understanding of how these interpretations have evolved and the potential implications for gender equality within Islamic thought. A qualitative approach was employed, focusing on textual analysis of selected Quranic verses, classical exegeses, and feminist readings. Data were gathered from prominent Islamic scholars and feminist scholars to compare and contrast the different interpretations of women’s roles in the Quran. The findings indicate a significant shift from traditional patriarchal interpretations towards feminist readings that emphasize gender equality and women’s empowerment. This research highlights the evolving nature of Quranic exegesis, where feminist scholars offer new insights into women’s agency and leadership. The study concludes that feminist interpretations of the Quran provide a more inclusive understanding of women’s roles, offering a foundation for advocating gender equality in contemporary Islamic discourse.